DENIED CHILD RIGHTS: CASE STUDY BAHA’I RELIGION IN PATI CENTRAL JAVA (International Conference on Social and Islamic Studies, 2021)
This article based on research carried out in 2020 among denied child rights the Baha'i religious in the village of Cebolek Kidul, Margoyoso, Pati, Central Java. Baha’i is an independent religionwas first known in Persia in 1840s and came to Indonesia in 1870 brought by medical expertsjoint a UN’s program and merchants. Data of this article were collected through interviews,observations, documentations and focus group discussion. In Cebolek, there are 25 people of 9 families. Article 71 of Act No.39/1999 the government is obligated to protect religious people. Indonesia acknowledge the existence of religion (anything) and facilitate all religion to grow, the same position in front of the law and the state does not interfere with the religious beliefs, but the state protect its citizens are religious anything. Minister of Religious Affairs, received a letter from the Minister of Home Affairs, No. 450/1581/SJ dated March 27, 2014 and answered him with a letter Number MA/276/2014 dated July 24, 2014 concerning an explanation of the existence of Baha'i in Indonesia (1) is one of the developing religions in 20 countries, (2) included in the religion protected in articles 29, 28 E, and 281 of the 1945 Constitution, (3) get full guarantee from the state, in the field of population, civil registration, education, law, etc. in accordance with the law. The civil service rights of the Baha'is in Pati have not yet been realized, even though the written explanation of the Secretary General of the Ministry of ReligiousAffairs, Bahrul Hayat, No SJ/B.VII/1/HM.00/675/2014 dated February 24, 2014 to theDirector General of Civil Affairs of the Ministry of Home Affairs, (1) Baha'i is a religion, therefore according to Article 29, 28E, and 28I of the 1945 Constitution, Baha'i religious peoplehave the right to live and worship according to their teachings, (2) Baha'is receive full guarantees from the state and are allowed, as long as they do not violate the provisions of the applicable laws, (3) in terms of population services, in accordance with Law No. 23/2006 jo with Law No.24/2013, Baha'is have the right to obtain population and civil registration services. But, the Ministry of Home Affairs has not yet issued a letter to the regional head so that the civil rights of the Baha'is have not all been served by the state, such as applications for marriage certificates. As a result, (1) certificate of birth the Baha'i children write by explisite “the child out of wedlock from the mother”, (2) the statuse of head of household a woman a married by man, (3) Baha’i children the labeling from environment a illegitimate child and labeling family get together. Therefore, UU No 35/2014 Article 72 (1) point G, social have to active participation negative remove about child impact minority group and stigmatization from public labeling .Government, national government group, and public joint us for protection Baha'i children.